Aborto Legal: Protocolo Assistencial do Hospital de Clínicas da Universidade Federal de Uberlândia - Basso, Denise Almeida Araújo (2024)
Introduction: In Brazil, abortion is permitted by law in cases when the life of the woman is at risk, the fetus is anencephalic, and the pregnancy is the result of sexual violence. In health services that provide care to patients who choose legal abortion, it is important that clinical practice be guided and standardized by protocols so that there is uniformity of clinical practice. Objective: The objective of this study was to develop the HC/UFU care protocol for health professionals caring for people who are pregnant and can have a legal abortion, based on current scientific evidence. Materials and Methods: The protocol was developed after a review of the main guidelines related to induced and safe abortion, following a search of the Pubmed and Tripdatabase databases, in response to clinical questions formulated in meetings with health professionals who care for patients who opt for legal abortion. Clinical guidelines from the database and website searches were appraised by two independent reviewers using the Appraisal of Guidelines for Research & Evaluation (AGREE II) tool. The recommendations were reviewed and approved in a meeting with service professionals. The recommendations were reviewed and approved in a meeting with service professionals. Results: Recommendations were made for medical and procedural management of legal abortion up to 14 weeks, between 14 and 24 weeks, and medical management of pregnancies over 24 weeks. Recommendations were also made for cervical preparation, prophylaxis and pain management. Conclusion: The HC/UFU protocol for the care of legal abortion has up-to-date recommendations based on quality guidelines, with good scores in the domains of the AGREE II instrument. The protocol also has local recommendations adapted to the limitations of techniques and supllies of the service.